Academic entrepreneurship creating an entrepreneurial ecosystem - Corbett, Andrew C.; Siegel, Donald S., 1959-; Katz, Jerome A. (Emerald, 2014)
Advances in entrepreneurship, firm emergence and growth provides an annual examination of the major current research in the field of entrepreneurship, including firm emergence and growth research. The Advances series also publishes papers from fields such as strategy or sociology that use entrepreneurial examples. It is a key source of articles-of-record for major concepts in the discipline of entrepreneurship. Volume 16 considers the central issue of academic entrepreneurship: the factors and concepts that underpin the fostering of university-based entrepreneurial ventures. Specifically, it contains research on the consequences of university technology transfer, with a strong emphasis on the entrepreneurial dimension of this activity. The theoretical and empirical manuscripts in this volume consider all aspects of how university stakeholders create, incubate, and accelerate ventures.
Keywords: Academic-industrial collaboration.; University-based new business enterprises.; elektronické knihy; electronic books